"The Rent Is Too Damn High": News Portrayals of Housing Security and Homelessness in the United States. Issue 4 (4th July 2021) - Borum Chattoo, Caty; Young, Lori; Conrad, David; Coskuntuncel, Aras
ABSTRACT: At any given moment across the United States, more than half a million people are experiencing homelessness, yet little is known about what Americans learn about contemporary housing security from the news. In response, this study presents a content analysis of every news story relating to housing security—inclusive of homelessness, affordable housing, and gentrification—published by 12 of the country's top-circulation metropolitan news outlets in 2018, located in the cities with the highest rate or recent increase in homelessness. Our data reveal that contemporary news portraits are failing to connect the intertwined dots of housing costs, gentrification, and homelessness; focus more attention on structural than individual causes of housing insecurity; overwhelmingly advance philanthropy as a solution for homelessness; and largely stigmatize members of historically marginalized racial and ethnic minority groups experiencing homelessness. This article presents a comprehensive news portrait about a complex social challenge, identifies paths for critical future research and points toward needed conversations within journalism institutions.